Combining Repetitive Transcranial Magnetic Stimulation and Video Game-Based Training to Improve Dexterity in Parkinson's Disease: Study Protocol of a Randomized Controlled Trial - Pastore-Wapp, Manuela; Lehnick, Dirk; Nef, Tobias; Bohlhalter, Stephan; Vanbellingen, Tim (Frontiers in Rehabilitation Sciences, 2021)
Introduction Patients with Parkinson’s disease (PD) often exhibit difficulties with dexterity during the performance of activities of daily living (ADL), due to dysfunctional supplementary motor area (SMA). The aim of this clinical trial protocol paper is to describe how investigate the effectiveness of a combined repetitive transcranial magnetic stimulation (rTMS) over SMA and video game-based skill training (VBT) in Parkinson's disease will be evaluated. The short and long-term benefits are assessed. We assume that the use of rTMS before VBT can further strengthen the training effects and possibly also achieve sustainable long-term effects. Methods and Analysis A single-blind (patients) stratified (based on Hoehn & Yahr) parallel randomized sham-controlled rTMS-VBT study with a baseline and two follow-up measurements (3 and 12 weeks) is being conducted. These measurements include the Dexterity Questionnaire 24 (DextQ-24) as a primary outcome, and Nine Hole Peg Test, Coin Rotation Task as main secondary dexterity outcomes. Further secondary outcomes will be the subscale II of the Movement Disorders Society unified Parkinson’s Disease Rating Scale (MDS-UPDRS) to assess improvements on overall ADL and the Parkinson Disease Questionnaire-39 to assess quality of life. Thirty-six outpatients (from one neurorehabilitation center) with PD (diagnosis based on brain bank criteria) will be recruited who report difficulties with dexterity in performing ADL. All PD patients will receive 45-minute VBT three times a week for three weeks. The PD patients randomized in the experimental group will receive VBT preceded by real rTMS, being intermittent theta burst (iTBS) stimulation sessions. The PD patients randomized to the control group receive a VBT with sham rTMS. Discussion The study will provide evidence to determine whether a combined iTBS and VBT skill intervention is more effective than a VBT intervention alone to improve dexterity in PD.